OPTIMALISASI PERAN SERTA MASYARAKAT DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI - Setiawan, I Ketut; Dawisni Manik Pinatih, SLP (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013)
Community participation in the fight against corruption is meant to embody the rights and responsibilities of the public in the administration of the state that is free and clean of corruption. In addition, with the participation of the public will be more aware to implement social control over corruption. The types of research used in writing this article is a kind of normative legal research norms contained in the law as well as to investigate and regulations regarding public participation in combating corruption. The conclusion from this study showed the maximum yet both quantitatively and qualitatively community participation towards eradicating corruption, so that the necessary transformation of the legislation ensures that more involvement of community participation towards eradicating corruption in the future.
Keywords: Community Participation, Corruption, State Administration, Social Control